Pengembangan Bahan Ajar Berbentuk E-Handout Konsep Sistem Pencernaan Manusia Fase F Di Madrasah Aliyah Negeri (MAN) - Hilmawati Ridhati; Noorhidayati Noorhidayati; Luthfiana Nurtamara (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The development of different teaching materials E-Handout on the Concept of Human Digestive System is one of the efforts to overcome the lack of understanding of Phase F students of MAN 2 Banjarmasin City. This study aims to develop E-Handout teaching materials and describe the suitability, feasibility, and readability of learners on the results of E-handout teaching materials development of human digestive system concepts. The development model used is 4D Thiagarajan (1974) which consists of stages 1) Define to define initial and final needs, 2) Design to select media and format, 3) Develop to assess research with suitability, feasibility, and readability assessment instruments, 4) Disseminate. This research was carried out to the stage of developing validation tests and validation tests. The research subjects were 3 validators consisting of 2 lecturers of Biology Education FKIP ULM and 1 partner teacher of MAN 2 Banjarmasin City, as well as 12 students of class XI (Phase F) specialization 1 biology MAN 2 Banjarmasin City. The results showed that 1) the results of the suitability test obtained a score of 4.20 (appropriate) with learning objectives, language, format, and media, 2) the results of the feasibility test obtained a score of 4.40 (very feasible) which means that technically E-Handout is very feasible to use as teaching material, 3) the results of the readability test obtained a score of 4.37 which means (very good) to be understood by students.Kata kunci: Pengembangan, Bahan ajar, E-Handout, Sistem pencernaan manusia.